Spectrophotometric Determination of Lamivudine - Appalaraju, S.; B. Karadi, Arvind; Kamalapurkar, O.S.; S. Sarasambi, Prakash (Asian Journal of Chemistry, 2010)
Three simple and sensitive spectrophotometric methods for the quantitative estimation of lamivudine in bulk drug and pharmaceutical formulations have been developed. The first method (Method I) is based on its diazotization with nitrous acid and subsequent coupling with phloroglucinol to form a yellow coloured species exhibiting absorption maximum at 445 nm and obeys Beer's law in the concentration range 2–10 g/mL. In the second method (Method II), the drug solution is reacted with Folin-Ciocalteau reagent in the presence of sodium carbonate solution to form a blue colour chromogen which has maximum absorption at 684 nm and obeys Beer's law in the concentration range 2–10 μg/mL. The third method (Method III) is based on the complex formation with 1,10- phenanthroline and Fe(III) exhibiting absorption maximum at 472 nm and obeys Beer's law in the concentration range 3–15 μg/mL. All coloured species are stable for more than 3 h. The results of analysis for all the three methods have been validated statistically and by recovery studies. The results of the above method are compared with the results of UV method which exhibited absorption maximum at 271 nm in alcohol.